Activation of the transcription factor NF-κB by retrieval is required for long-term memory reconsolidation - Merlo, E. (2005)
Several studies support that stored memories undergo a new period of consolidation after retrieval. It is not known whether this process, termed reconsolidation, requires the same transcriptional mechanisms involved in consolidation. Increasing evidence supports the participation of the transcription factor NF-κB in memory. This was initially demonstrated in the crab Chasmagnathus model of associative contextual memory, in which re-exposure to the training context induces a well characterized reconsolidation process. Here we studied the role of NF-κB in reconsolidation. NF-κB was specifically activated in trained animals re-exposed to the training context but not to a different context. NF-κB was not activated when animals were re-exposed to the context after a weak training protocol insufficient to induce long-term memory. A specific inhibitor of the NF-κB pathway, sulfasalazine, impaired reconsolidation when administered 20 min before re-exposure to the training context but was not effective when a different context was used. These findings indicate for the first time that NF-κB is activated specifically by retrieval and that this activation is required for memory reconsolidation, supporting the view that this molecular mechanism is required in both consolidation and reconsolidation.